BALAGEO: Website Etnomatematika untuk Materi Pemecahan Masalah Teorema Pythagoras dalam Konteks Budaya Lokal - Yasha, Say-in; Sulistyaningsih, Dwi; Dian Mawarsari, Venissa (Program Studi Pendidikan Matematika FIP UNHASY, 2026)
Problem-solving ability is one of the essential competencies in mathematics learning. However, many students still experience difficulties in solving mathematical problems because learning activities are often not connected to real-life contexts. Integrating digital learning media with local cultural contexts can be an alternative approach to create more meaningful learning experiences. This study focuses on the development of a website-based mathematics learning media called BALAGEO. BALAGEO learning media integrates ethnomathematical elements from the Rawa Pening boat race into the topic of the Pythagorean theorem. The study employed a Research and Development approach using the ADDIE development model, which includes analysis, design, development, implementation, and evaluation stages. The developed media was tested on eighth-grade students at SMP Negeri 1 Bawen. Media feasibility was evaluated through expert validation involving material and media experts, while its practicality was determined based on responses from teachers and students after the implementation. The findings indicate that the BALAGEO website achieved a very valid category based on expert assessments and was considered highly practical by users. These results suggest that integrating ethnomathematics into website-based learning media can support more contextual and engaging mathematics learning, particularly in the topic of the Pythagorean theorem.